The Rising of “Modern Actinobacteria” Era - Jodi Woan-Fei Law; Vengadesh Letchumanan; Loh Teng-Hern Tan; Hooi-Leng Ser; Bey-Hing Goh; Learn-Han Lee (Progress In Microbes & Molecular Biology, 2020)
The term “Modern-Actinobacteria” (MOD-ACTINO) was coined by a Malaysian Scientist Dr. Lee LearnHan, who has great expertise and experience in the field of actinobacteria research. MOD-ACTINO is defined as a group of actinobacteria capable of producing compounds that can be explored for modern applications such as development of new drugs and cosmeceutics. MOD-ACTINO members consist of already identified or novel actinobacteria isolated from special environments: mangrove, desert, lake, hot spring, cave, mountain, Arctic and Antarctic regions. These actinobacteria are valuable sources for various industries which can contribute directly/indirectly towards the improvement in many aspects of our lives.